DETERMINATION OF ABSORPTION LINE PARAMETERS FOR СО2 10°0–00°1 TRANSITION FROM ABSORPTION COEFFICIENT MEASUREMENTS BY TUNABLE СО2 LASER - V. V. Nevdakh; K. I. Arshinov; M. K. Arshinov (Приборы и методы измерений, 2015)
The unsaturated absorption coefficients in pure CO2 at the pressures 1 and 100 Torr and in CO2:N2  and CO2:He binary gas mixtures at the pressure 100 Torr are measured in the 296-700K temperature range by a frequency-stabilized tunable CO2 laser. The coefficient of Einstein Amn, CO2 self-broadening coefficient, the relative optical broadening coefficients in CO2 due to the presence of foreign gases N2 and He and its temperature dependences are obtained for the R22 line of CO2 1000-0001 transition.